Planners between the Chairs: How Planners (Do Not) Adapt to Transformative Practices - Othengrafen, Frank (2019)
Even though the turn to practice is widely accepted in the field of urban planning, the practices of planners are empirically largely unexplored. Looking at the daily routines and practices of urban planners thus allows a deeper insight into what planning is, and how planning practices are related to innovation and transformation. To do so, we start from the assumption that behaviour is a constellation of practices, including certain activities, a set of choices and actions, patterns of behaviour or forms of interaction that is organised in a certain space or context by common understandings and rules. By conducting an online survey among planners in medium-sized German cities, we first identified a wide range of planning practices and activities in general. In a second step, we conducted a statistical cluster analysis resulting in six types of planners: (1) the ‘local-specific analysts,’ (2) the ‘experienced generalists,’ (3) the ‘reactive pragmatists,’ (4) the ‘project-oriented planners,’ (5) the ‘compensatory moderators,’ and (6) the ‘innovative designers.’ Each cluster has specific practices and activities, linked to characteristic value-sets, role interpretations and self-perceptions that might help explain the differences with regard to innovation and transformation. From the identified six groups or clusters of planners, only two clusters more or less consequently aim at innovation, experimentation and new approaches. One cluster is dedicated to collaborative practices whereas traditional practices predominate in three clusters at least, mainly because of legal requirements. This is the result of an increasing ‘formalisation’ of land-use planning, making planners focus on technical and formal practices, and, at the same time, lead to the reduced ‘attention’ to and implementation of conceptual approaches or ‘necessary’ transformative practices, including proactive approaches and strategic coordination with regard to sustainable urban development, but also comprising experiments, real labs or social innovations.